Negotiating cultures and identities : life history issues, methods, and readings - Caughey, John L., 1941- (University of Nebraska Press, 2006)
"Negotiating Cultures and Identities examines issues, methods, and models for doing life history research with individual Americans based on interviews and participant observation. John L. Caughey helps students and other researchers explore the ways in which contemporary Americans are influenced by multiple cultural traditions, including ethnic, religious, and occupational frames of reference. Using the example of Salma, a bicultural woman of Pakistani descent who lives in the United States, and the story of Gina, a multicultural American, Caughey examines how to capture the complexity of each situation, including step-by-step methods and exercises that lead the student interviewer through the process of locating and interviewing a research participant, making sense of the material obtained, and writing a cultural portrait. Arguing that comparison between the subject's life and one's own is an essential part of the process, the methodology also encourages the investigator to research his or her own social and cultural orientations along the way and to contrast these with those of the subject. The book offers a practical, manageable, and engaging form of qualitative research. It prepares the student to do grounded, experiential work outside the classroom and to explore important issues in contemporary American society, including ethnicity, race, identity, disability, gender, class, occupation, religion, and spirituality as they are culturally understood and experienced in the lives of individual Americans. Book jacket."--BOOK JACKET.